A COMPARATIVE STUDY OF NEMATODA FACILITIES OF SHORTAGE PLANTS AND TREES IN ZARAFSHAN FOREST BIOTOPES (Academicia Globe: Inderscience Research, 2022)
The main goal of our research is to compare the nematodefauna of wild sugar cane root and rhizosphere growing in the Zarafshan tugai biotope with the nematodafauna of trees (black willow) growing in this biotope, and the degree of similarity is Mountford generality. was reported to be 25.81. Also, when we compared the nematodes found in the root and peripheral soil of wild sugar cane and rhubarb retail plants, it was found that there was a sharp difference between them. The results were recorded as 12.14 on the Mountford Overall Index.